2016
DOI: 10.1186/s12986-016-0134-6
|View full text |Cite
|
Sign up to set email alerts
|

Dietary selenium augments sarcoplasmic calcium release and mechanical performance in mice

Abstract: BackgroundAs an essential trace element selenium plays a significant role in many physiological functions of the organs. It is found within muscles as selenocystein in selenoprotein N, which is involved in redox-modulated calcium homeostasis and in protection against oxidative stress.MethodsThe effects of two different selenium compounds (selenate and NanoSe in 0.5 and 5 ppm concentration for two weeks) on muscle properties of mice were examined by measuring in vivo muscle performance, in vitro force in soleus… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
22
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 28 publications
(23 citation statements)
references
References 46 publications
1
22
0
Order By: Relevance
“…We also found beneficial effects of selenium on both in vivo and in vitro muscle function and, in addition, on calcium homeostasis in aged mice. The fact that selenium has similar positive effects on muscles from young 9 and aged animals (this study) underlines its potential application in the treatment of sarcopenia.…”
Section: Mismatch Between Muscle Mass and Contractile Force Our Resusupporting
confidence: 59%
See 3 more Smart Citations
“…We also found beneficial effects of selenium on both in vivo and in vitro muscle function and, in addition, on calcium homeostasis in aged mice. The fact that selenium has similar positive effects on muscles from young 9 and aged animals (this study) underlines its potential application in the treatment of sarcopenia.…”
Section: Mismatch Between Muscle Mass and Contractile Force Our Resusupporting
confidence: 59%
“…i) Since RyR1 is very sensitive to oxidative changes, its accommodation to oxidative stress through conditioning with lifelong training could improve the calcium channel functions as demonstrated by the decreased degradation of RyR1 in trained animals. ii) As RyR1 degradation was not reduced in selenium supplemented aged animals, nevertheless selenium as an antioxidant increased muscle performance both in young 9 and aged animals (this study), RyR1 independent pathway(s) should also underlie the observed effects.…”
Section: Effects Of Long Term Training On Muscle Performancementioning
confidence: 61%
See 2 more Smart Citations
“…Muscle contractions were measured as described previously [46]. Briefly, EDL muscles were placed horizontally in an experimental chamber.…”
Section: Measurement Of Edl Muscle Forcementioning
confidence: 99%